EVALUATION IN ARABIC LEARNING - Fatimah, Fatimah (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2021)
This article explains the importance of evaluation as one of the learning components, particularly in Arabic teaching and learning. In the learning process there are two main activities, namely learning done by the students and teaching done by the teacher, the two activities are to achieve the objectives set out in the lesson plan. In this article, readers are invited by the author to discuss various matters related to the evaluation of Arabic learning, such as the objectives and principles of evaluation, the variety of evaluation, and the signs in the preparation of test equipment, whether test or non test techniques. Keyword: Evaluation, learning, model, technique, test, and non test